IMC: PROMOSI, IKLAN DAN SPONSOR ROKOK STRATEGI PERUSAHAAN MENGGIRING REMAJA UNTUK MEROKOK - Ardy Dharmawan Salim (Benefit: Jurnal Manajemen dan Bisnis, 2013)
Marketing communication strategies of tobacco companies more incentive and innovative.This is because competition between tobacco companies and the rise of anti-smoking campaigns.But tobacco company marketing communications strategy often used youth as its target market, asevidenced by the promotion, advertising and sponsorship that uses style, icon and all imagingabout teenagers. Not only that, music events, school, sports, etc are thepreferred young childrenand adolescents followed into areas of marketing tobacco products either directly or indirectly,such as sponsorship